DECONSTRUCTION OF THE PATRIARCHAL MYTH OF ADAM AND EVE IN CONTEMPORARY ARABIC LITERATURE - Latifi, Yulia Nasrul (Adabiyyāt: Jurnal Bahasa dan Sastra, 2025)
This study aims to highlight Arab women’s autonomy by elaborating the feminist meaning in the literary code that challenges the patriarchal myth of Adam and Eve in three contemporary Arabic literary works. Through a feminist literary criticism approach, this study reveals the form of deconstruction and criticism of the binary opposition. Hence, Eve (woman) becomes a complete subject who gives birth and not who is born. The narrative-symbolic argument of these works is based on historical-logical-scientific and theological-rationalistic thinking styles. The purpose of the deconstruction in them is to create the autonomy of women with noble dignity as human beings, as men are. The deconstruction reflects the thought of progressive muslim authors who believe in and advocate for the substantive value of the holy Koran, particularly its emphasis on egalitarianism in the myth of Adam and Eve.